2016
DOI: 10.1002/jbm.b.33625
|View full text |Cite
|
Sign up to set email alerts
|

Lithium doped calcium phosphate cement maintains physical mechanical properties and promotes osteoblast proliferation and differentiation

Abstract: Calcium phosphate cement (CPC) has been widely used in bone tissue repairing due to its physical mechanical properties and biocompatibility. Addition of trace element to CPC has shown promising evidence to improve the physical properties and biological activities of CPC. Lithium (Li) has effect on osteoblast proliferation and differentiation. In this study, we incorporated Li to CPC and examined the physical properties of Li/CPC and its effect on osteoblast proliferation and differentiation. We found that Li d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…2B). Combined with the results shown above, which consistently reflected HA formation, we concluded that Li/CPC had favourable bioactivity in vitro to the same extent as that of CPC, a finding that is in accordance with other reports23.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2B). Combined with the results shown above, which consistently reflected HA formation, we concluded that Li/CPC had favourable bioactivity in vitro to the same extent as that of CPC, a finding that is in accordance with other reports23.…”
Section: Resultssupporting
confidence: 92%
“…Li/CPC was prepared according to a method described previously23. TTCP (Sigma–Aldrich, Saint Louis, MO, USA) and DCPA (Sigma–Aldrich) were mixed at a ratio of 1:1 as a powder phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using human osteosarcoma (MG63) cells, several studies in recent years also reported that lithium had promising effects on osteoblast proliferation and differentiation. Lithium-doped CPC had high biocompatibility, supported osteoblast attachment and growth, and promoted cell proliferation and differentiation in MG-63 cells (Li et al, 2017b). It was noteworthy that MG-63 cells cultured on bone substitute coated with lithium had higher cell viability, cell proliferation, cell differentiation, calcium deposition, and expression of osteogenesis-related genes (Guo et al, 2018;Liu et al, 2018;Ma et al, 2019).…”
Section: Effects Of Lithium On Osteoblastogenesismentioning
confidence: 95%